Strawgirl - Kay J. Jackie (London, Macmillan Children's books, 2002)
A beautiful, extraordinary, first novel for children from a unique storyteller. Growing up on a Highland farm in a totally white community, 11-year-old 'Maybe' MacPherson hates her mixed-race roots: she is half Celtic and half Nigerian lbo. But everything changes when her beloved father is killed in a car accident. Faced with running the farm herself and coping with her grief-stricken mother, Maybe needs all her strength to fight the local bullies - and the farm's unscrupulous owners, who want to sell the farm to a supermarket chain. Suddenly, at harvest time, Strawgirl enters Maybe's life - an extraordinary, magical girl made from straw who will help Maybe not only to discover who she really is, but also the courage that lies within her.